2000
DOI: 10.1016/s1468-6996(00)00009-7
|View full text |Cite
|
Sign up to set email alerts
|

High-strength Zr-based bulk amorphous alloys containing nanocrystalline and nanoquasicrystalline particles

Abstract: It was recently found that the addition of special elements leading to the deviation from the three empirical rules for the achievement of high glass-forming ability causes new mixed structures consisting of the amorphous phase containing nanoscale compound or quasicrystal particles in Zr-Al-Ni-Cu-M (M Ag, Pd, Au, Pt or Nb) bulk alloys prepared by the copper mold casting and squeeze casting methods. In addition, the mechanical strength and ductility of the nonequilibrium phase bulk alloys are significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 27 publications
(45 reference statements)
2
68
0
Order By: Relevance
“…5(a)). It is reported that the mechanical strength and ductility of the bulk glassy alloy can be significantly improved by the formation of the nanostructures as compared with the corresponding glassy single phase alloys in Zr-AlCu-Pd 6) and Zr-Ti-Ni-Cu-Al 17) alloys. The authors 13) also found that both the mechanical strength and ductility of the Ti-Zr-Cu-Pd bulk glassy alloy can be significantly enhanced by the formation of the nanostructures after appropriate annealing treatment, leading to the dispersion of the nanoparticles which may act as inhibitor against shear deformation of the glassy matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5(a)). It is reported that the mechanical strength and ductility of the bulk glassy alloy can be significantly improved by the formation of the nanostructures as compared with the corresponding glassy single phase alloys in Zr-AlCu-Pd 6) and Zr-Ti-Ni-Cu-Al 17) alloys. The authors 13) also found that both the mechanical strength and ductility of the Ti-Zr-Cu-Pd bulk glassy alloy can be significantly enhanced by the formation of the nanostructures after appropriate annealing treatment, leading to the dispersion of the nanoparticles which may act as inhibitor against shear deformation of the glassy matrix.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) The ex-situ technique is charactered by the introduction of extraneous fibres or particles into bulk metallic glasses before casting process. 1,3) In-situ formed composites can be synthesized trough annealing of metallic glass precursors, [4][5][6][7] and slightly adjusting composition 2,8) or cooling rate of the cast glasses 9,10) to produce a metallic glass matrix with dispersed crystalline phases. The bulk metallic glass composites show significantly improved plastic deformation comparing with the monolithic glass.…”
Section: Introductionmentioning
confidence: 99%
“…This subject requires further research, in light of the importance of ductility for applications. On the other hand various attempts have been made to improve ductility primarily by mixing with soft and ductile crystalline materials [48,77,78].…”
Section: Ductilitymentioning
confidence: 99%
“…Partially devitrified Al-based and Zr-based amorphous alloys are of great interest for their good mechanical properties such as high tensile strength, high bending strength, high Charpy impact toughness and high fatigue strength [1][2][3][4][5][6][7][8][9] due to their fine microstructure, termed as nanocomposite. For example, a tensile fracture stress as high as 1560 MPa has been reported in an Al-based nanophase composite.…”
Section: Introductionmentioning
confidence: 99%
“…11) Several different models for the strengthening mechanism in partially devitrified amorphous nanocomposite materials have been proposed. Inoue et al 2) attributed high strength and good ductility of the bulk nanocrystalline alloy to i) an enhancement of the resistance to shear deformation of the amorphous matrix caused by the nanoscale particle which has a perfect crystal structure with ideal high strength and ii) the effects of amorphous matrix which has a localized deformation mode due to a high density of free volumes, residual compressive stress field and multiple axis stress field. Greer proposed a matrix solute enrichment model 12) which attributed the strengthening of partially or fully devitrified alloys to the solute enrichment of the remaining amorphous phase, and described that hardness of the nanocomposite would be simply that of the glassy matrix.…”
Section: Introductionmentioning
confidence: 99%